??????????? ?? ???????: ????? ???????? ??????? ??????? ??????? ?? ????? ????? ??????? - Muhammad Toha (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2017)
Technology is the evidence of progress achieved by human in science. By having technology, some instruments and means are improving to help people solve some problems of life. When researchers ask education practitioners about technology, surely they will say that technology is the use of instruments and means perfectly to help people do the daily activities. Technology also should be used in teaching-learning process at school so that it will be more effective to deliver the materials to students. The process of learning can run better by using technology than the previous era which did not use technology, especially in learning of reading skill. Aurora 3 Dimensions (3D) program is one of the computer programs which provides 3 dimensions and eye looking picture, so that students will be interested in learning reading skill. Hopefully Aurora 3 dimensions technology will influence significantly in improving students’ reading competence. Teknologi adalah bukti kemajuan yang dicapai manusia dalam bidang pengetahuan. Karena dengannya berkembanglah instrumen dan piranti untuk membantu manusia dalam memecahkan problematika hidup. Ketika peneliti bertanya kepada para praktisi pendidikan tentang teknologi, tentu mereka akan menjawab bahwa teknologi adalah penggunaan instrumen dan piranti secara sempurna untuk membantu manusia dalam melakukan aktifitas sehari-hari. Teknologi juga harus digunakan dalam proses pembelajaran di sekolah yang berpeluang memudahkan penyampaian materi ajar kepada siswa. Dengan adanya teknologi proses pembelajaran bisa berjalan lebih baik dibanding masa sebelum penggunaan teknologi utamanya dalam pembelajaran keterampilan membaca. Program tiga dimensi (3 D) Aurora adalah salah satu program komputer yang mampu menghasilkan tampilan gambar dalam bentuk tiga dimensi dan eye looking sehingga akan membuat siswa tertarik dalam pembelajaran keterampilan membaca. Semoga teknologi tiga dimensi (3D) Aurora akan berpengaruh secara signifikan dalam meningkatkan kemampuan membaca siswa.